Adsorption Study of Fructosyltransferase Immobilization By Using Various Adsorbent - Nor Hazwani Syuhada, Azmi (2013)
Immobilized enzyme are widely used in the industry because of its stability and economic. Because of the high demand from the industry, the research is done in order to enhance the quality of immobilized enzyme. This study discusses about the adsorption in the enzyme immobilization process. The purposes of this study are to find out the species of sawdust (Keruing, Meranti and Kempas) which have the excellent adsorption capability, to investigate the effect of various initial enzyme concentrations and the time required for the adsorption of adsorbate onto adsorbent reach equilibrium. For the immobilization process, it was occurred in water bath shaker for 26 h at room temperature and at pH 5.5. The enzyme activity was analyzed by using DNS method. To determine the equilibrium time, the solutions was being agitated in water bath shaker at 100 rpm and the samples were taken out at a given time intervals for analyses (0-40 hours). The concentration of FTase was analyzed by using UV-Vis Spectrometer. The effect of various initial enzyme concentrations (0, 2, 4, 6, 8, 10, 12, and 14 g/L) in the adsorption process was analyzed by using UV-Vis Spectrometer and employing Langmuir and Freundlich models in order to find out the isotherm which fit with the data obtained.SEM and FTIR was done to identify the structures of the untreated, treated sawdust and immobilize enzyme. All the three adsorbents had achieved the equilibrium at time 25 to 30 hours and it is showed that Keruing adsorbent comes out with the highest loading capacity (0.945g of FTase/L) due to the size of pores itself. Enzyme concentration residue increases after the addition of 6 g/L of FTase due to the amount of enzyme were exceeds the amount of adsorbent. Freundlich isotherms fitted the data while Keruing showed the highest capability of adsorption followed by Meranti as adsorbent.